Development of Models for Express Analysis of Road Safety - L. S. Abramova; H. H. Ptitsia; S. V. Kapinus; T. V. Kharchenko (Наука и техника)
Results of a study of an actual scientific and technical problem of determining the road safety level on road sections are presented in the paper. The aim of the study is to develop an express method for assessing road safety based on improving the method of the final accident rate by reducing the partial accident rate with the required accuracy of determining the safety level on public roads. The formalization of the relationship between the parameters of road traffic conditions has been carried out to study the level of safety on highways. Latent factors of the parameters of traffic conditions have been obtained on the basis of reduction of their aggregate by the method of principal components, taking into account the relationship of partial accident rates. This condition has allowed to develop analytical models for determining road safety for implementation in the practice of conducting a road safety audit. A method for identifying hazardous areas on highways has been proposed in the paper. It includes 11 parameters of road conditions out of 18 partial accident rates proposed in the prototype and regulatory documents of Ukraine. The adequacy of the model is determined by deviation values of the obtained data according to the prototype model from the values of the relative accident rate, which were 3.22 and 18.61, respectively. The proposed model reduces the deviation value by six times and affects the accuracy of determining the safety level. Experimental studies have been conducted on 79 km of highways (on 385 sectors with constant values of traffic conditions parameters). The results of a comparative analysis of the safety level for the prototype model and the developed model have been identical and shown a decrease in time and labor costs by 1.6 times without loss of accuracy. Thus, the developed methodology is recommended to be applied for determining the potential danger of road sections during an express analysis of the road safety or when conducting a safety audit at various stages of the road life cycle.